CANDI IJO DALAM PERSPEKTIF WISATAWAN MANCANEGARA - Bayu Grendoe Sigarete; Halim Ahmad (Politeknik Negeri Bengkalis, 2017)
Abstract: Ijo temple is one of the attractions visited by tourist, not only domestic but also foreign tourists. Thus, in its development, needs and desires of tourists also had to be accommodated in order to maximize the potential benefits from tourism activities in Ijo temple. This paper discusses the perspective of foreign tourists to the Ijo temple. This study used descriptive qualitative method. The results showed that the foreign tourists who visit Ijo temple think that Ijo temple is a charming attraction. But there are some things that need improvement include infrastructure, services, and facilities. Keywords: Perspectives, tourists, Ijo temple